Effects of physical pretreated oil palm frond on body weight and feed convertion ratio of the Boer goats - Zaid Ahmad Mohd Zamri (2018)
Ruminant livestock production in tropical country such as Malaysia has lack of grazing pasture and difficulty to provide feed with sufficient quantities and nutrient through the years. This makes the feed cost at the market is expensive. Oil palm frond (OPF) has been used as one of the alternative biomasses for animal feed because it’s low cost and readily available daily. However, OPF cannot be fed solely due to its poor nutrition content and low digestibility. OPF also contains high lignocellulosic content. Thus, OPF has to be pretreated to improve its nutrition contents. The objective of this study is to evaluate the physical pretreatment of OPF on body weight (BW), body score condition (BCS) and the feed conversion ratio of the goat. The OPF were collected and transported to the Agro Technopark, UMK Campus Jeli, Kelantan. The whole OPF underwent physical pretreatment by pressing OPF using sugarcane machine. The goats were divided into three group; control group (70% Napier grass, 30% pellet) treatments 1 (50% Napier grass, 30% pellete, 20% chopped OPF) and treatment 2 (50% Napier grass, 30% pellete, 20% pressed OPF) for 168 days. All groups were fed with napier grass and commercial goat pellet to make it isonitrogenous. For performance evaluation, the goats were weighed for every two weeks while the body condition score assessed once per month. Based on the finding, T1 and T2 groups show high significantly (p<0.05) different than control group. This shows that OPF give positive affect to the body weight gain of Boer goat. In addition, the average daily gain and feed conversion ratio in physically pressed OPF group was higher than chopped OPF and napier grass treatment.